Educational Management Practices of Islamic Religious Education Teachers in Developing Students’ Character in Elementary Education - Habibullah; Sugiono (Journal of Educational Management Research, 2026)
Character education is a fundamental component of elementary education, requiring not only pedagogical efforts but also effective educational management practices. This study aims to analyse how Islamic Religious Education (IRE) teachers implement educational management practices in developing students’ character through role modelling, religious habituation, and humanistic interaction. Using a qualitative case study approach, the research involved IRE teachers, school principals, classroom teachers, and students as key informants. Data were collected through classroom observations, in-depth interviews, and documentation, and analysed using an interactive analysis model. The findings indicate that IRE teachers play a managerial role in character education by planning and modelling moral values such as honesty, responsibility, and respect; organising structured religious practices that foster discipline and order; and implementing humanistic interactions that reinforce moral development through empathetic communication and persuasive approaches. These practices collectively function as an integrated educational management process that supports character formation beyond formal instruction. The study implies that strengthening students’ character requires schools to recognise IRE teachers as key actors in educational management and to institutionalise role modelling, habituation, and relational practices as part of school-wide character governance.